Prevalence, Incidence, and Metabolic Characteristics of Young Adults with Type 2 Diabetes Mellitus in South Korea (2010–2020) - Ji Yoon Kim; Jiyoon Lee; Joon Ho Moon; Se Eun Park; Seung-Hyun Ko; Sung Hee Choi; Nam Hoon Kim (Diabetes & Metabolism Journal)
Background This study aimed to examine trends in the prevalence, incidence, metabolic characteristics, and management of type 2 diabetes mellitus (T2DM) among young adults in South Korea. Methods Young adults with T2DM were defined as individuals aged 19 to 39 years who met the diagnostic criteria for T2DM. Data from the Korean National Health Insurance Service-Customized Database (2010–2020, n=225,497–372,726) were analyzed to evaluate trends in T2DM prevalence, incidence, metabolic profiles, comorbidities, and antidiabetic drug prescription. Additional analyses were performed using the Korea National Health and Nutrition Examination Survey. Results The prevalence of T2DM in young adults significantly increased from 1.02% in 2010 to 2.02% in 2020 (P<0.001), corresponding to 372,726 patients in 2020. Over the same period, the incidence rate remained stable within the range of 0.36% to 0.45%. Prediabetes prevalence steadily increased from 15.53% to 20.92%, affecting 3.87 million individuals in 2020. The proportion of young adults with T2DM who were obese also increased, with 67.8% having a body mass index (BMI) ≥25 kg/m² and 31.6% having a BMI ≥30 kg/m² in 2020. The prevalence of hypertension, dyslipidemia, and fatty liver disease also increased, reaching 34.2%, 79.8%, and 78.9%, respectively, in 2020. Although the overall pharmacological treatment rate remained low, the prescription of antidiabetic medications with weight-reducing properties increased over the study period. Conclusion The prevalence of T2DM among young adults in South Korea nearly doubled over the past decade. The strong association with obesity and metabolic comorbidities emphasizes the urgent need for targeted prevention and management strategies tailored to this population.